Kebijakan Larangan Pembangunan Ritel Modern dan Pemberdayaan Pedagang Kecil di Banyuwangi - Wilda Rasaili (Research and Development Agency Ministry of Home Affairs, 2020)
The government's strategy in minimizing the modern market space was first implemented by the banyuwangi regency government trough a policy prohibiting the contruction of malls and retails modern. this policy in concidered unpopular because impedes invesment and regional income. the theory used in this study is public policy and community empowerment with discriptive-explanatory research methods. The research of this study indicate that the policy prohibits the construction of malls and retails modern as strategy of local government to empower small traders. This policy has real impact on economic inprovement and poverty reduction significantly